2022
DOI: 10.3390/jcm11133844
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Impact on SARS-CoV-2 Infection: Pros and Cons “Obesity Paradox”—A Systematic Review

Abstract: Background: During the last years, the COVID-19 pandemic meets the pandemic generated by obesity, raising many questions regarding the outcomes of those with severe forms of infection. Methods: The present systematic review summarises and analyses the data providing evidence for or against the “obesity-paradox” in COVID-19 patients. After applying the inclusion and exclusion criteria, 23 studies were included. We also analysed the presumably underlying basic mechanisms. Results: The patients with a body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 93 publications
3
11
0
Order By: Relevance
“…We also found that BMI was interdependent within pairs. Further, our findings indicate that higher BMI may be associated with higher symptom burden, which is consistent with several other studies pointing to obesity as a risk factor for more severe disease progression ( 39 , 43 47 ).…”
Section: Discussionsupporting
confidence: 92%
“…We also found that BMI was interdependent within pairs. Further, our findings indicate that higher BMI may be associated with higher symptom burden, which is consistent with several other studies pointing to obesity as a risk factor for more severe disease progression ( 39 , 43 47 ).…”
Section: Discussionsupporting
confidence: 92%
“…The association between the FMI and the BMI with mortality was not demonstrated. This lack of association is consistent with the results in several studies included in an interesting systematic review, (23) in which it is shown that there is an association between the high fat mass with hospital admission, severity of the disease, orotracheal intubation, among others, but with a contradictory association with mortality. The limitations of this study should be borne in mind.…”
Section: Discussionsupporting
confidence: 89%
“…Smoking led to an upregulation of ACE2 with an increased risk of severe disease[ 91 ]. Another condition that predicts severe outcomes is obesity[ 92 ]; it increased intensive care unit (ICU) admission and the requirement of invasive mechanical ventilation[ 93 ]. Also, attention should be taken in psychiatric patients (with anxiety and depression) because some possible associations between these comorbidities and sleep problems were reported[ 94 ].…”
Section: Clinical Course Of Sars-cov-2 Infectionmentioning
confidence: 99%